Study Analysis of TSS Distribution Around Teluk Lamong Area Using Remote Sensing and Numerical Modeling Approach - Muhammad Ilham Maulana; Widi Agus Pratikto; Suntoyo Suntoyo (International Journal of Marine Engineering Innovation and Research, 2022)
The Surabaya coast is a strategic area for sustainable development. For example, Teluk Lamong Harbor was built using reclamation. The port can be a solution but also has a coastal ecological impact. Therefore, a study of the coastline and distribution of the TSS was carried out around the Lamong Bay area. Based on the analysis of shoreline changes, the addition in the west (Kali Lamong) with NSM and EPR reached 166 m and 16.6 m/year and in the east, there was an addition (Osowilangon) with NSM and EPR reaching 337 m and 33.7 m/year. Based on TSS analysis by satellite, TSS in 2012 in the east had an average of 28.42 mg/L, increasing in 2017 to 36.39 mg/L, increasing again in 2022 with a value of 38.46 mg/L. While in the west in 2012, the high TSS had an average concentration of 40.95 mg/L, increasing in 2017 to 44.57 mg/L, increasing again in 2022 with a value of 52.68 mg/L. The modeling results show that the average TSS (west) in 2012 is ±20 mg/L, while in 2022 it is ±60 mg/L. In the east port, the average concentration of TSS in 2012 and 2022 did not change significantly (±20 mg/L).